A Review of Isolation, Chemical Properties, and Bioactivities of Polysaccharides from Bletilla striata. (27th May 2020) - Ji, Xiaolong; Yin, Mingsong; Nie, Hui; Liu, Yanqi
Abstract : Recently, polysaccharides from Bletilla striata, a member of the orchidaceous family, aroused the wide interest of people, especially their isolation, chemical properties, and bioactivities. It is reported that these polysaccharides are the most important biologically active components of B. striata, exhibiting various biological activities, such as immunomodulatory, antioxidant, antifibrotic, and hemostatic effects. This review appraised the available literatures which described different aspects of B. striata polysaccharides, including the extraction, separation, purification, structural characterization, and biological activities. We expect to lay the foundation for further investigation of the application of B. striata polysaccharides in the field of functional foods and biomedicine.